2012
DOI: 10.1371/journal.pone.0046930
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Bearing in Citrus: Changes in the Expression of Flowering Control Genes and in Global Gene Expression in ON- versus OFF-Crop Trees

Abstract: Alternate bearing (AB) is the process in fruit trees by which cycles of heavy yield (ON crop) one year are followed by a light yield (OFF crop) the next. Heavy yield usually reduces flowering intensity the following year. Despite its agricultural importance, how the developing crop influences the following year's return bloom and yield is not fully understood. It might be assumed that an ‘AB signal’ is generated in the fruit, or in another organ that senses fruit presence, and moves into the bud to determine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
103
0
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(127 citation statements)
references
References 62 publications
14
103
0
10
Order By: Relevance
“…In satsuma mandarin, CiFT expression increases during fall and winter, in which period floral induction occurs. This increase results from the expression of CiFT2 which is also induced during fall and winter in murcott mandarin (Citrus reticulate Blanco) (Shalom et al, 2012). In kumquat and trifoliate orange, CiFT expression increases during early summer, in which period evocation of flower organs has been initiated, or just before evocation.…”
Section: ) Identification Of Flowering-related Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…In satsuma mandarin, CiFT expression increases during fall and winter, in which period floral induction occurs. This increase results from the expression of CiFT2 which is also induced during fall and winter in murcott mandarin (Citrus reticulate Blanco) (Shalom et al, 2012). In kumquat and trifoliate orange, CiFT expression increases during early summer, in which period evocation of flower organs has been initiated, or just before evocation.…”
Section: ) Identification Of Flowering-related Genesmentioning
confidence: 99%
“…Recently, changes in gene expression in response to fruit bearing have been reported in 'Murcott' (C. reticulata Blanco) (Shalom et al, 2012) -Fambuena et al, 2011), and satsuma mandarin (Nishikawa et al, 2012). In these genotypes, the levels of CiFT expression seem to be high in light-fruiting "off" trees and low in heavy-fruiting "on" trees during the floral inductive period.…”
Section: ) Suppression Of Cift Expression By Fruit Bearingmentioning
confidence: 99%
“…The suppression of CiFT expression by fruit bearing indicates that CiFT expression is correlated to alternate bearing. Recent studies have attempted to identify the mechanism of al- ternate bearing through proteomic or transcriptomic analysis (Muñoz-Fambuena et al, 2013a, b;Shalom et al, 2012Shalom et al, , 2014. However, further studies are needed to understand fully the alternate bearing in citrus.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in the off-crop trees, the presence of a smaller amount of sink tissues may lead to the accumulation of sugar phosphates as well as starch in the stem. It has been reported that the expression of some of the genes and proteins involved in the Calvin cycle is up-regulated in off-crop trees (Muñoz-Fambuena et al, 2013b;Shalom et al, 2012). Therefore, it is suggested that fruit bearing affects not only gene expression or protein levels but also the levels of substrates in the Calvin cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation